The Involvement of Nitric Oxide in Integration of Plant Physiological and Ultrastructural Adjustments in Response to Arsenic - Farnese, Fernanda S.; Oliveira, Juraci A.; Paiva, Elder A. S.; Menezes-Silva, Paulo E.; da Silva, Adinan A.; Campos, Fernanda V.; Ribeiro, Cléberson (Frontiers in Plant Science, 2017)
High arsenic (As) concentrations are toxic to all the living organisms and the cellular response to this metalloid requires the involvement of cell signaling agents, such as nitric oxide (NO). The As toxicity and NO signaling were analyzed in Pistia stratiotes leaves. Plants were exposed to four treatments, for 24 hours: control; SNP (sodium nitroprusside (NO donor); 0.1 mg L-1); As (1.5 mg L-1) and As + SNP (1.5 and 0.1 mg L-1, respectively). The absorption of As increased the concentration of reactive oxygen species (ROS) and triggered changes in the primary metabolism of the plants. While photosynthesis and photorespiration showed sharp decrease, the respiration process increased, probably due to chemical similarity between arsenate and phosphate, which compromised the energy status of the cell. These harmful effects were reflected in the cellular structure of P. stratiotes, leading to the disruption of the cells and a possible programmed cell death. The damages were attenuated by NO, which was able to integrate central plant physiological processes, with increases in non-photochemical quenching and respiration rates, while the photorespiration level decreased. The increase in respiratory rates was essential to achieve cellular homeostasis by the generation of carbon skeletons and metabolic energy to support processes involved in responses to stress, as well to maintaining the structure of organelles and prevent cell death. Overall, our results provide an integrated view of plant metabolism in response to As, focusing on the central role of NO as a signaling agent able to change the whole plant physiology.